MINERAL CONTENT OF SURFICIAL SEDIMENT OF THE RANGSANG ISLAND AND ITS SURROUNDING AREA, MERANTI REGENCY, ARCHIPELAGO RIAU PROVINCE - Deny Setiady; Ediar Usman (Marine Geological Institute of Indonesia, 2015)
According to the regulation No 4 of 2009 of Mineral and Coal Mining Management stated that the requirement of an inventory for mineral resources data was created to support the establishment of mining area. This study is intended to obtain mineral resources content and surficial sediment data, Geographically the study area belongs to Meranti Archipelago Regency, Riau Province. it is located between 102o00'00